Diabetes in Pregnancy - Neema Acharya; Monisha Singh; Sandhya Pajai (A Concise Clinicopathological Handbook of Diabetes Mellitus, 2021)
Pregnancy is a diabetogenic condition physioloigicaly.Incidence of diabetes in pregnancy is increasing globally. This chapters covers the effects of diabetes on pregnancy and effect of pregnancy on pre-existing diabetes. The disease has adverse fetomaternal outcomes. Early detection and good glycemic control achieves good outcomes. Multidisciplinary approach should be followed in management of this medical disorder in pregnancy.